Heat transfer analysis of tomato root zone temperature cooled by chilled water in tropical greenhouse - Ho, Angelina Mei Yi (2011)
The effect of root zone cooling on tomato root density was investigated under a greenhouse structure at Malaysian Agricultural Research and Development Institute (MARDI). Heat tolerance tomato variety was grown in a tropical greenhouse with preinstalled buried cooling pipes to chill the root zone. The experiment was conducted in a Split Plot Design with 4 temperature treatments, 15'C, 20'C, 25'C and the control (with no cooling pipes installed, approximately 30'C). Each treatment has 3 replicates. The results revealed that cooling the root zone to 25'C, the optimum temperature of tomato root volume production, increased the root volume by 32% at 16 Weeks after Transplanting (WAT), 7% at 20 WAT and 3% at 24 WAT. The study also shows that most of the roots are concentrated on the top layer which is first 10cm below the surface of planting media. The thermal conductivity and thermal diffusivity of a planting media inside a tropical greenhouse was investigated and experimentally measured using the line heat source transient method. The apparatus used in this study was a modified thermal needle probe. The planting media used in this greenhouse was a combination of cocopeat: burnt rice husk: perlite with a ratio of 7:3:2 respectively. The thermal conductivity of cocopeat: burnt rice husk: perlite at a ratio of 7:3:2 with moisture content, 55.98% wet basis, and density, 0.08 g/cm' was 0.1164 w/m'C; and the thermal diffusivity was 1.1063 x 10-4m'/s. At higher moisture content, the thermal conductivity of the planting media was 0.1560 w/m'C; while the thermal diffusivity was 7.9029 x 10-4m'/s. Finally, a heat transfer analysis on the cooling system applied to the root zone was done. The effect of heat inside the greenhouse and the cooling effect from the pipes to the root zone temperature were studied. Calculations were done using a Solver for Principles of Heat Transfer. A heat transfer model was then developed to predict the root zone temperature using the conservation of energy concept where surface radiation heat transfer into the planting media is equals to the surface convection heat transfer of the chilled planting media.